FACILITY CHARACTERISTICS ASSOCIATED WITH CARE DEFICIENCIES IN ASSISTED LIVING. (11th November 2018) - Lerner, N; Trinkoff, A M; Storr, C L; Han, K; Yoon, J; Kyum Yang, B
Abstract: In the US, assisted living facilities (ALFs), have been increasing in number, and are caring for residents with progressively higher needs. Since ALFs are state regulated, there are no US-level outcomes data available. This analysis used a newly available database of ALF care deficiencies from one US state. Severe deficiencies (potential or actual patient harm) were related to facility size, nursing staff availability (licensed nurses and aides) using Chi-Square and logistic regression. Larger facilities (>100 beds) had higher rates of severe deficiencies compared to small ALFs s (4–10 beds). We then stratified by facility size, due to interaction with nurse availability. Among larger ALFs, the odds of severe deficiencies were greater in ALFs without 24-hour nursing availability. Further outcome data is needed to evaluate and monitor quality in ALFs. Increased research on those facility characteristics improving outcomes is needed